Occupation of Synoeca surinama (L.) (Vespidae, Polistinae) nests by Nasutitermes obscurus (Holmgren) (Termitidae, Nasutitermitinae) in the Cerrado - Jacques, Gabriel de Castro; Francisco, Sheliane Cristina Coelho; Rubim, Luis Gustavo Talarico; Souza, Marcos Magalhães de (EntomoBrasilis, 2023)
The study of relationships between living beings is essential for understanding the functioning of the ecosystem for the management and conservation of biota, especially in rich and threatened biomes such as the Brazilian Cerrado. Therefore, this study aims to report the occupation of abandoned social wasp’s nests by termites in this biome. In this study, the occupation of two abandoned nests of Synoeca surinama (L.) by the termite Nasutitermes obscurus (Holmgren), recorded by chance, in April 2023 in a gallery forest with the same vegetation type of the Cerrado, located in the Grande Sertão Veredas National Park in southeastern Brazil. Both social wasp nests had their cells occupied by termites, which may have been used as a satellite nest for N. obscurus. This is the first record of a termite species occupying a social wasp’s nests; however, further studies are needed to better elucidate this relationship.